The Influence of Work Flexibility on Job Satisfaction and Performance of Generation Z - Pradipta, Dian; Adzani, Riva Almira; Perkasa, Didin Hikmah (Journal of Applied Business Administration, 2025)
This study examined the influence of work flexibility and job satisfaction on performance among Generation Z employees at the Indonesian Ministry of Defense Office. This study comprised a saturated sample of 107 participants. This paper utilized a quantitative analysis using survey methodology, questionnaires, and structural analysis techniques with Smart-PLS. The study’s findings indicated that Work Flexibility has a significant positive effect on Job Satisfaction. Work flexibility significantly affects employees' assessment of their level of satisfaction. Flexible work arrangements allow individuals to optimize their time management and increase job satisfaction. Job satisfaction will inherently improve employee performance.